Personal Records Management and its Impact on the Civil Service Pension Payment System in Tanzania - Msuya, J.; Lyaruu, T.M. (Ghana Library Journal, 2008)
If study was carried to examine the management of personal records in public sector and its impact on the payment of pension to retired Dublic servants. A total of 65 respondents were involved in the study (rom three different ministries and one government agency. Non orobability sampling method was used to obtain the sample. Questionnaire, interviews and observation methods were used to obtain the data. The study revealed that the state of persona I records management is not satisfactory. The information available in the files is incomplete and in some cases inaccurate. Lack of skills and knowledge in records management, poor and inadequate facilities,communication breakdown, negligence and meagre allocation of resources are some of the constraints fa cing records management departments. The impact of this is the persistent delays in payment of pension to beneficiaries. The study recommends among others, formulation of organizational records management policy, staff training, automation of records management practices and creation ofa master files f or all public servants.